The The Behavior Rate of Return on Banking Deposit During Covid-19 in Indonesia - Rozaq Muhammad Yasin; Nurzahroh Lailyah; Keke Tamara Fahira (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The crisis condition caused by the pandemic had an impact on financial performance in general, including the policy on the rate of return provided by banks. This study aims to analyze the behavior of bank deposit returns during Covid-19 in Indonesia. Using time-series data for the period February 2020 – September 2021 which was analyzed using the VECM approach, it shows that there is a long-term relationship between the returns on Islamic Rural Bank, Islamic commercial bank, rate of interest, and deposit Insurance Agency interest rates. Meanwhile, in the short-term relationship, only the DIA variable is significantly influenced by the previous period's DIA variable. The results of the study found that the DIA variable was proven to significantly affect the rate of return given by IRB and conventional bank deposit rates. During the Covid-19 pandemic, banks provided a rate of return on deposits that did not exceed the DIA guarantee interest rate. The banking industry and DIA need to mitigate risks that arise during the Covid-19 pandemic.